The Implementation of Process-Based Approach in Online Teaching Writing in SMA Bali Hati - Putu Dinda Mirahayu (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study described the process-based approach implemented for Senior High School students and the challenges of teaching writing in an EFL setting for online classrooms during the pandemic of Covid-19. It was conducted at SMA Bali Hati in the academic year 2020-2021. The study applied a single instrumental case study in which the data were collected through an interview guide, observation sheet, and documentation. The result showed that the preparation was done in the online class. In addition, several problems were faced during the implementation. The results of the study indicate that teachers need to find alternatives to address the challenges.